Development and Validation of Liquid Chromatography Method for Simultaneous Estimation of Metformin, Pioglitazone, and Glimepiride in Bulk and Pharmaceutical Dosage Form - R. Karthikeyan (Asian Journal of Pharmaceutics (AJP), 2025)
A simple reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous determination of Metformin hydrochloride, Pioglitazone, and Glimepiride in their pharmaceutical dosage form. The validated technique proved to be suitable for routine QA applications. Method: The chromatographic separation was achieved using Agilent C18 column (250 mm × 4.6) 5 μm as a stationary phase with mobile phase composition of Methanol and Tris buffer (pH 8) in ratio of 65:35 v/v. The mobile phase was then sonicated for 10 min and then filtered through 0.45 μm membrane. The flow rate was 1 mL/min isocratic, column temperature 40°C, and ultraviolet detection at λ 227 nm. Conclusion: The retention times for metformin, pioglitazone, and glimepiride were found to be 1.227 min, 3.843 min, and 7.353 min, respectively. The RP-HPLC technique was validated using the International Council for Harmonisation (ICH) guidelines. Recovery, precision, accuracy, selectivity, and robustness of the method were evaluated according to the ICH guidelines. This method is simple, rapid, convenient, and a perfect choice for the determination of metformin, pioglitazone, and glimepiride from bulk and pharmaceutical formulations.